2022
DOI: 10.1021/acschembio.2c00060
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandins Localized to the Target-Harboring Cell Surface Are Not Degraded but Those Entering the Vacuole Are

Abstract: Echinocandin antifungal drugs have a broad spectrum of activities and excellent safety profiles. These agents noncompetitively inhibit the formation of the major polysaccharide component of the fungal cell wall, a reaction catalyzed by the membrane-bound β-glucan synthase (GS) protein complex. We have developed fluorescent probes of three echinocandin drugs: caspofungin (CSF), anidulafungin (ANF), and rezafungin (RZF). Fluorescent echinocandins had the same spectrum of activities as the parent echinocandins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…anidulafungin, and rezafungin. [46,47] Imaging of live Candida cells incubated with the fluorescent echinocandins revealed that those derived from caspofungin accumulate in vacuoles of the yeast cells, and those derived from anidulafungin localize to the yeast cell surface; rezafungin-derived probes appeared on the yeast cell surface shortly after their introduction but accumulated in vacuoles after a longer incubation period (Figure 3). Since Fks is a membranebound protein, accumulation of the echinocandin on the cell surface increases its local concentration in proximity to the target.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…anidulafungin, and rezafungin. [46,47] Imaging of live Candida cells incubated with the fluorescent echinocandins revealed that those derived from caspofungin accumulate in vacuoles of the yeast cells, and those derived from anidulafungin localize to the yeast cell surface; rezafungin-derived probes appeared on the yeast cell surface shortly after their introduction but accumulated in vacuoles after a longer incubation period (Figure 3). Since Fks is a membranebound protein, accumulation of the echinocandin on the cell surface increases its local concentration in proximity to the target.…”
Section: Methodsmentioning
confidence: 99%
“…To study the subcellular distributions of echinocandins, their mechanisms of entry into fungal cells, and the relationship between their uptake and antifungal activity, Fridman and co‐workers prepared fluorescently labeled caspofungin, anidulafungin, and rezafungin [46, 47] . Imaging of live Candida cells incubated with the fluorescent echinocandins revealed that those derived from caspofungin accumulate in vacuoles of the yeast cells, and those derived from anidulafungin localize to the yeast cell surface; rezafungin‐derived probes appeared on the yeast cell surface shortly after their introduction but accumulated in vacuoles after a longer incubation period (Figure 3).…”
Section: Echinocandinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] To study the subcellular distributions of echinocandins, their mechanisms of entry into fungal cells, and the relationship between their uptake and antifungal activity, Fridman and co-workers prepared fluorescently labeled caspofungin, anidulafungin, and rezafungin. [46,47] Imaging of live Candida cells incubated with the fluorescent echinocandins revealed that those derived from caspofungin accumulate in vacuoles of the yeast cells, and those derived from anidulafungin localize to the yeast cell surface; rezafungin-derived probes appeared on the yeast cell surface shortly after their introduction but accumulated in vacuoles after a longer incubation period (Figure 3). Since Fks is a membranebound protein, accumulation of the echinocandin on the cell surface increases its local concentration in proximity to the target.…”
Section: Echinocandinsmentioning
confidence: 99%
“…[6][7][8] The efficacy, tolerability, and favorable pharmacokinetic profile of echinocandins have contributed to their widespread adoption, particularly in managing infections caused by azole-resistant Candida pathogens. [8][9][10] Four echinocandins have been approved for clinical use: caspofungin, micafungin, anidulafungin, and, most recently (March of 2023), rezafungin. (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%